2007
DOI: 10.1136/oem.2006.027789
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported health problems and sickness absence in different age groups predominantly engaged in physical work

Abstract: Objectives: To study the associations between self-reported health problems and sickness absence from work. Methods: The results of a questionnaire survey were combined with archival data of sickness absence of 1341 employees (88% males; 62% blue-collar) in the construction, service and maintenance work within one corporation in Finland. Sex, age and occupational grading were controlled as confounders. A zero-inflated negative binomial (ZINB) regression model was used in the statistical analysis of sickness ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 33 publications
6
87
1
4
Order By: Relevance
“…Similar results, indicating that younger workers may be more susceptible to the effects of work, have been found, for example in a prospective study on the predictors of low-back pain (23) as well as in relation to sickness absence (24). The age modification in productivity loss may partly be explained by health-based selection.…”
Section: Discussionsupporting
confidence: 67%
“…Similar results, indicating that younger workers may be more susceptible to the effects of work, have been found, for example in a prospective study on the predictors of low-back pain (23) as well as in relation to sickness absence (24). The age modification in productivity loss may partly be explained by health-based selection.…”
Section: Discussionsupporting
confidence: 67%
“…27 The response variable in this study was assumed to be a count variable, and the choice of the best adjusted model followed steps recommended in the literature. [25][26][27][28] Among the variables of the domain "perception of the neighborhood", fear of falling because of sidewalk defects was significant in both components of the model. Among elderly subjects that had difficulty in carrying out ADL, the presence of this concern meant a 62.0% increase in the expected number of ADL accomplished with difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…The alternatives for analysis are attempts of transformation to normality or categorization of variables, which may result in loss of information. 26,27 A possible approach is to assume a Poisson distribution. In applying the Poisson regression model (PRM), we found that the data was overdispersed (the mean number of ADL done with difficulty differed from the variance).…”
Section: Discussionmentioning
confidence: 99%
“…To increase retention, organizations should explore strategies to maintain and improve working conditions (including shiftwork and psychosocial factors) and sustain healthcare workers' health and work ability as they age. Ageing is typically associated with decreased physical health, while the relationship between ageing and outcomes such as job satisfaction, absenteeism and injuries is more controversial, with studies indicating that being older may actually protect employees (Beatty and Burroughs, 1999;Ingersoll et al, 2002;Taimela et al, 2007).…”
Section: Ageing and Shiftworkmentioning
confidence: 99%